Identification and documentation of herbicide resistance - Heap, I.M. (Phytoprotection, 1994)
Proactive herbicide resistance management programs rely upon early detection of resistant populations and knowledge of which combinations of weed and herbicide are prone to the development of resistance. Annual weeds that are prolific seed producers, genetically diverse, and repeatedly exposed to a single herbicide mode of action, are prone to rapid development of resistance. When resistance is suspected, seed samples are collected and evaluated using a whole plant bioassay. Whole plant bioassays are conducted underfield, growth room, or Petri dish conditions. Complete dose response curves for the suspected resistant and a reference susceptible population are used to verify resistance. Bioassay, conducted in growth rooms, is the most reliable method for identification of new cases of herbicide resistance. Bioassays, based on the biochemical detection of a single mechanism of resistance, are not reliable for screening for new occurrences of resistance.